No Increased Coronary or Mortality Risk Associated with Changes in DAPT - Nierengarten, Mary Beth (MD Conference Express, 2014)
For patients discharged after acute coronary syndrome (ACS), changing from dual-antiplatelet therapy (DAPT) to less potent antiplatelet therapy is not associated with increased coronary or mortality risk despite a short-term excess of cardiovascular (CV) events. This article presents the results of the Long-term Follow-up of Anti-thrombotic Management Patterns in Acute Coronary Syndrome Patients [EPICOR; NCT01171404], a real-world-practice cohort study conducted to describe current international patterns of DAPT use following ACS and the clinical outcomes associated with changes in DAPT.